Avaliação das condições estomatológicas de pacientes portadores de hidrocefalia congênita - Pereira, Maria Auxiliadora Silva (2005)
The aim of this study was to evaluate the stomatologic conditions of patients with congenity hydrocephaly. Thirty children with congenity hydrocephaly were examined with ages between 2 and 6.5 years, from both genders, admitted at Governador João Alves Filho General Hospital and in the University Hospital in the city of Aracaju-SE and 34 children from both genders were also included. It was analyzed with a clinical examination the variables related to the gingival bleeding index, oral hygiene index, the ceo-d index, for the presence of dental anomalies, eruption timing, soft tissue alterations and palatus. The data collected were analyzed with the t test qui square and Fisher and p < 0.05. The results obtained showed that in the Group of Patients with Congenity Hydrocephaly (GPCH), there was a predominance of moderate gingivitis, while the majority of healthy children, there wasn t any gingivitis (p < 0.05), with statistic difference, the oral hygiene was regular with the GPCH and good with the healthy children, also seen statistical differences. In case of the ceo-d index, it was not observed any significant statistical differences, being the ceo-d total of 1.53 and 1.44 for the GPCH and for the healthy children, respectively. However, it was informed that they didn t see any fillings on any teeth of the GPCH proving a significant statistical difference, but the presence of squamous tongue, fissured tongue, labial frenulum and late eruption were verified only on children with congenity hydrocephaly. The atresic palatus was most prevalent in these patients comparing to the healthy children. Therefore, the children with congenity hydrocephaly present worst oral health conditions than the healthy children, suggesting they belong to a group of patients with special needs, by that, being fundamental a greater attention to the oral health, with the participation of the dentist in the team involved on the care of these patients.